The right apparoach to effective herbicide application - Lourdes Nathan (RB Field Sdn Bhd, No 12, Jalan U1.77, Taman Perindustrian Batu Tiga, 40500 Shah Alam, Selangor (Malaysia)) (2013)
This paper highlights the importance of some factors to be considered by the Planter to allow him to make the right decisions when embarking on a spraying programme in his estate. Issues addressed in this paper include maximum utilisation of equipment, ways to reduce chemical wastage, improvement of operator safety standards, reduction in downtime, care and maintenance of the equipment for an effective spraying campaign.